Cognitive Effects of Transcranial Direct Current Stimulation in Healthy and Clinical Populations: An Overview. Issue 3 (September 2018) - Berryhill, Marian E.; Martin, Donel
Abstract : Abstract: Transcranial direct current stimulation (tDCS) is a neuromodulatory approach that is affordable, safe, and well tolerated. This review article summarizes the research and clinically relevant findings from meta-analyses and studies investigating the cognitive effects of tDCS in healthy and clinical populations. We recapitulate findings from recent studies where cognitive performance paired with tDCS was compared with performance under placebo (sham stimulation) in single sessions and longitudinal designs where cognitive effects were evaluated following repeated sessions. In summary, the tDCS literature currently indicates that the effects of tDCS on cognitive measures are less robust and less predictable compared with the more consistent effects on motor outcomes. There is also a notable difference in the consistency of single-session and longitudinal designs. In single-session tDCS designs, there are small effects amid high variability confounded by individual differences and potential sham stimulation effects. In contrast, longitudinal studies provide more consistent benefits in healthy and clinical populations, particularly when tDCS is paired with a concurrent task. Yet, these studies are few in number, thereby impeding design optimization. While there is good evidence that tDCS can modulate cognitive functioning and potentially produce longer-term benefits, a major challenge to widespread translation of tDCS is the absence of a complete mechanistic account for observed effects. Significant future work is needed to identify a priori responders from nonresponders for every cognitive task and tDCS protocol.